KINERJA DAN PERBANYAKAN PARASITOID TETRASTICHUS BRONTISPAE PADA HAMA DAUN KELAPA : BRONTISPA LONGISSIMA GESTRO (COLEOPTERA : CHRYSOMELIDAE) DI KABUPATEN ENDE-FLORES - Wahyuni, Sri (Agriculture Faculty of Flores University, 2010)
Brontispa longissima Gestro (Coleoptera: Chrysomelidae) is one of the important pests that attack the palm plants in Southeast Asia. There is a reported decline in the productivity of palm plants when the pest attack reaches 30-40% with 5% of the plants attacked dying. B. longissima pest attacks plants at all stages of life, but its attack is most prevalent when plants reach the age of 4-5 years. The spread of pest B. longissima has ben reported in the district of Ende, Nangakeo and Ndona in 13 villages with a total area of the severe intensity of attacks. There have been attempted control measures with the release of natural enemies Tetratichus brontispae but not much success has be seen. This study aimed to find out: The dominant type of parasite in the district of Ende. T. brontispae were propagated and maintained in the laboratory using augmentation techniques, conservation or disposal was to be done. Colonies of the propagated parasite T. brontispae were then released in the field. The factors causing T. brontispae control failure, the population of B. longissima in the field, possibly the need for augmentation or conservation of T. brontispae and the right time to make the release of the parasite in the field was important. This research is expected to be useful as a basis in formulating and appropriate control program, in order to control the pest B. longissima in the field. The experiment was conducted from January to June 2010 at Nangakeo, Ndona and Ende district. Implementation of the research was divided into four stages: location survey, maintenance and multiplication of the pests B. longissima and T. brontispae parasite, parasite release and the evaluation of the result. The result was; that there are three types of parasites, B. longissima coconut leaf pest in Ende (sub Ndona, Nangakeo and Ende) the eggs of the parasite Trichogrammatoideanana spp., the larvae and pupae of the parasite Trichogrammatoideanana spp. and the ?Asecodeshispinarum Boucek?. T. brontispae parasite being the most dominant parasite in each district with 10% level of larvae and pupae of 60-90%, biased sex male : vemale ratio. The pest capability of T. brontispae parasite in the laboratory was 6: 10 with a success rate of 90 %. The decline in the influence of parasite performance was unsynchronized between phases from the phase of the insect host-parasite in the field, the availability of insect host and time of release as well as climatic conditions not being conductive.